A MODIFICATION OF TIBREWALA, PHILIPPE, AND BROWNE'S ALGORITHM FOR MULTI-SHIFT MANUFACTURING WORKERS SCHEDULING - Wahyudi, Adhie Tri; Zendrato, Rosleini Ria Putri; Indrasari, Anita; Suparti, Erni; Prayuda, Fendi; Cahyawati, Amanda Nur (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2024)
The SME under study, which specializes in hard wooden and leather furniture for foreign markets, encountered difficulties in integrating their make-to-order production system with tight shipping export deadlines. This necessitated a systematic worker scheduling technique in order to satisfy production targets and reduce labor expenditures. The aim of this research was to design a worker scheduling system to ensure that the production makespan corresponded to the available time limitations. The study found that the Tibrewala, Philippe, and Browne algorithm for multi-shift workers scheduling significantly reduced labor costs while ensuring order fulfillment within predefined constraints, emphasizing the need for additional research that includes all production cost variables for more comprehensive cost savings.